• An Approach to the Relations between Language and Politics: The Image of Justice - Bazo Ráez, Percy Alberto (2007)
This article seeks to demonstrate the political scope of language. Thus, for the author, society codifies and transmits experiences through language; and this implies that it is a system of categories that legitimizes the social practice of a community. For a better understanding, the author relies on some conceptions about justice, and in this way, he mentions the goddesses of justice, Themis and Iustitia, and the modifications they had throughout history. These modifications would indicate differences in the way of understanding and establishing intersubjective relations between ancient and modern societies. For this reason, the author points out that language not only communicates the identity of a people, but is also a necessary condition for a more just social order, since the lack of coexistence between the mother tongue and the practical reality translates into a violation of the rights of those who do not speak the predominant language.